2017
DOI: 10.1177/2158244017702198
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model of Determinants of the Perceived Impact of Teachers’ Professional Development—The Abu Dhabi Application

Abstract: The purpose of this study is to use statistical evidence to better understand professional development impact and its causal determinants. The study creates a plausible structural equation model (SEM) and tests it. This study uses Abu Dhabi teacher's data drawn from the Teaching and Learning International Survey (TALIS) 2013. A sample of 4,941 teachers from public and private schools participated in the study. The proposed model represented the hypothesis that the latent variable impact of professional develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…However, the present study has demonstrated how the teachers' perceptions-accurate or otherwise-of their own expertise affected their attitudes toward (and, therefore, the impact of) professional development. For more objective studies of teacher professional development in Abu Dhabi at the time this study was conducted, we refer readers to Badri et al (2017) and Von Oppell and Aldridge (2015).…”
Section: Limitationsmentioning
confidence: 99%
“…However, the present study has demonstrated how the teachers' perceptions-accurate or otherwise-of their own expertise affected their attitudes toward (and, therefore, the impact of) professional development. For more objective studies of teacher professional development in Abu Dhabi at the time this study was conducted, we refer readers to Badri et al (2017) and Von Oppell and Aldridge (2015).…”
Section: Limitationsmentioning
confidence: 99%
“…Teacher PD should also be balanced and coordinated with school evaluation and feedback systems. The perceived effect of PD, according to researchers, represents how carefully chosen programs are to respond to their perceived needs (Badri et al, 2017; Kennedy, 2016). Stoll et al (2012) stated that PD and practice focusing would significantly impact the students’ progress.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived Impact (IM1–IM3) of PD was also investigated with the question from section E on the questionnaire, and the last section F questions also analyzed the Feedback Effect (FE1–FE3) on PD. Items used to measure the questionnaire were selected from the research by Badri et al (2017), Goe et al (2012), Saleem et al (2021), Shernoff et al (2018), and Tuytens and Devos (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the professional development program stems from an awareness of a need, effective assessment plays an important role in supporting learners and enhancing their ability to take on new responsibilities in other learning environments (Badri et al, 2017). Regarding the group learning component, Eraut (2004) describes three types of work activity in the professional development environment that give rise to the acquisition of knowledge and skill, namely participation in group activities (including team-work), working alongside others (and gaining a new perspective from colleagues), and tackling challenging tasks (which can increase confidence and problem-solving abilities).…”
Section: The Third Component: Process Factorsmentioning
confidence: 99%